2014
DOI: 10.1111/pim.12137
|View full text |Cite
|
Sign up to set email alerts
|

Filariasis asymptomatically infected donors have lower levels of disialylated IgG compared to endemic normals

Abstract: Helminths induce strong regulatory and T helper 2-type responses, whereby antibody-derived host protection and regulation are essential components. Lymphatic filariasis is an immune-mediated spectral disease that manifests as two main clinical outcomes: chronic pathology or asymptomatic infection. These outcomes depend on a multitude of factors, including parasite-induced immunoregulation and host genetic background; antibody responses contribute to this outcome. N-glycosylation of the Fc region of antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
2
7
1
Order By: Relevance
“…FA2 has been shown to predominantly originate from IgG 40 , 41 . While a previous study has reported changes in the IgG sialylation in people infected with a related filarial nematode, W. bancrofti 36 , our analysis revealed no change in IgG N-glycan microheterogeneity in dogs with a patent D. immitis infection. We do, however, see an increased abundance of serum IgG in infected dogs that is likely responsible for at least part of the change in the relative abundances of serum N-glycans.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…FA2 has been shown to predominantly originate from IgG 40 , 41 . While a previous study has reported changes in the IgG sialylation in people infected with a related filarial nematode, W. bancrofti 36 , our analysis revealed no change in IgG N-glycan microheterogeneity in dogs with a patent D. immitis infection. We do, however, see an increased abundance of serum IgG in infected dogs that is likely responsible for at least part of the change in the relative abundances of serum N-glycans.…”
Section: Discussioncontrasting
confidence: 90%
“…Further, it is noteworthy that D. immitis is closely related to O. volvulus , W. bancrofti and B. malayi , causative agents of onchocerciasis and lymphatic filariasis afflicting more than 135 million humans 33 , 34 , thus making our results relevant for a wider filariasis research community. While alterations in IgG N-glycosylation have previously been associated with leishmaniasis 35 , asymptomatic filariasis 36 and other parasitic infection in developing countries 37 to the best of our knowledge, this is the first report of drastic changes in the mammalian total serum N-glycosylation profile as a consequence of parasitic infections.…”
Section: Introductionmentioning
confidence: 66%
“…In this study, distinct glycosylation features of IgG1 and IgG2 and -3 that determine the inflammatory and regulatory functions of IgG molecules and possibly cognate functions of antibodies were associated with outcomes of infections with L. infantum chagasi . Several studies have addressed the composition and role of IgG Fc N-glycans in human infectious diseases; e.g., global IgG galactosylation is significantly perturbed in patients with tuberculosis ( 25 ); patients with hepatitis C virus who develop cirrhosis present increased levels of agalactosylated IgG specific for alpha-Gal epitope [Gal-1-3Gal1-(3)4GlcNAc-R] ( 40 ); antiviral activity is modulated by natural variations in Fc glycosylation of HIV-specific antibodies ( 27 ); the opsonizing capacity of IgG for hepatitis B virus depends on the profile of Fc glycosylation, which is also associated with clinical outcomes of infection with this virus ( 41 ); and individuals asymptomatically infected with Wuchereria bancrofti had significantly lower levels of disialylated IgG than endemic controls and patients with pathology ( 42 ). However, the analytical techniques applied in those studies did not discriminate between IgG subclasses and/or registered overall glycosylation but not Fc-specific glycosylation or did not detail specific Fc glycosylation profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The patients elicit a strong T helper (Th)1 and Th17 immune response that eliminate the microfilarial stage [5] while inducing the production of angiogenic factors like VEGF known to be associated with the development of filarial lymphedema [6]. This severe clinical profile is characterized by high antigen-specific immunoglobulin (Ig)E and low IgG4 [5] [7,8]. The third group includes asymptomatic individuals with latent infection who are free of microfilaria (Mf-) but are positive for circulating filarial antigens (CFA) [9].…”
Section: Introductionmentioning
confidence: 99%